A Dissipation Function–Based Method for Calculating the Energy Loss of Intracranial Aneurysms - Mo, Xiao; Yu, Hongshi; Chen, Rong; Chen, Zhenpeng; Li, Haiyun (Frontiers in Neurology, 2021)
At present, the energy loss (EL) mechanism of intracranial aneurysms (IAs) rupture is explored based on the global EL calculated by Bernoulli equation, but the details of EL are still unclear. This study aimed to explore the temporal and spatial characteristics of EL of IAs, and reveal its mechanism. A novel method for calculating the EL of IAs based on dissipation function (DF) was proposed. DF was derived from the differential form of the energy equation and reflected the irreversible conversion from mechanical energy to internal energy caused by the friction between the fluid micelles. Eight sidewall IAs located at the internal carotid posterior communicating artery were collected, the 3D geometric models of IAs were established employing image segmentation and 3D reconstruction. Computational fluid dynamics (CFD) was applied to obtain hemodynamic parameters of IAs. The temporal and spatial characteristics of EL of IAs were achieved utilizing our proposed method. The simulation results indicated that EL occurred mainly in the boundary layer and the region adjacent to high-velocity inflow jet, EL increased rapidly during cardiac systole and reached its maximum at end-systolic phase, then decreased gradually during diastole until the end of cardiac cycle. The proposed method achieved some improvements over the traditional Bernoulli's equation-based method by acquiring the temporal and spatial characteristics of EL, and it could provide insights into the EL of IAs and contribute to further rupture mechanism investigation.